A simple grand canonical approach to compute the vapor pressure of bulk and finite size systems - Factorovich, Matias Hector (2014)
In this article we introduce a simple grand canonical screening (GCS) approach to accurately compute vapor pressures from molecular dynamics or Monte Carlo simulations. This procedure entails a screening of chemical potentials using a conventional grand canonical scheme, and therefore it is straightforward to implement for any kind of interface. The scheme is validated against data obtained from Gibbs ensemble simulations for water and argon. Then, it is applied to obtain the vapor pressure of the coarse-grained mW water model, and it is shown that the computed value is in excellent accord with the one formally deduced using statistical thermodynamics arguments. Finally, this methodology is used to calculate the vapor pressure of a water nanodroplet of 94 molecules. Interestingly, the result is in perfect agreement with the one predicted by the Kelvin equation for a homogeneous droplet of that size.